Individual patient data (IPD) meta-analysis of the London measure of unplanned pregnancy (LMUP) as used in Cape Town, South Africa - Rashid, Zahra Zameer (Department of Public Health and Family Medicine, 2025)
Background: Global estimates report approximately 44% of pregnancies are unintended, with the incidence being significantly higher in developing countries. In South Africa, it has been found that 51% of pregnancies are unintended. Extensive research has shown that unintended pregnancies are associated with an increased risk of significant health consequences for both mother and child, making it an important metric for the state of maternal and child health. The aim of this study is to evaluate the performance of the London Measure of Unplanned Pregnancy (LMUP) for the measurement of pregnancy intention in Cape Town, South Africa and investigate the prevalence and factors associated with unintended pregnancy in this setting. Methods: This secondary analysis collected baseline data from 5404 pregnant women seeking antenatal care and enrolled in one of the four included research studies in Cape Town, South Africa that utilized the LMUP to measure pregnancy intention. Data was collected from March 2013 to October 2023 and collated into a single database. The performance of the LMUP was measured using Cronbach's α test. The prevalence of unintended pregnancy was calculated, and factors associated with unintended pregnancy were explored using linear mixed-effects regression methods. Results: The LMUP performed well overall (Cronbach's α = 0.84) and similarly within the four studies. Unplanned pregnancies were high at 40% overall. Participant age and maternal gestational age at entry into antenatal care were found to be strongly associated with pregnancy intention (p < 0.001), with women who are younger and women presenting later for antenatal care more likely to be having an unplanned pregnancy. However, HIV status was not found to be significantly associated with pregnancy intention. Conclusions: These findings indicate that unintended pregnancies are incredibly high in this setting in spite of relatively easy access to sexual and reproductive health services including contraceptives. This calls for an evaluation and improvement of current offerings in sexual and reproductive health services – particularly for younger women – to reduce the incidence of unplanned pregnancy, improve maternal and child health, and strengthen women's agency in decisions around family planning.